2015
DOI: 10.1111/jpy.12317
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the freshwater raphidophyte Gonyostomum semen confirms a recent expansion in northern Europe by a single haplotype

Abstract: Gonyostmum semen is a freshwater raphidophyte that has increased in occurrence and abundance in several countries in northern Europe since the 1980s. More recently, the species has expanded rapidly also in north-eastern Europe, and it is frequently referred to as invasive. To better understand the species history, we have explored the phylogeography of G. semen using strains from northern Europe, United States, and Japan. Three regions of the ribosomal RNA gene (small subunit [SSU], internal transcribed spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(108 reference statements)
1
8
1
Order By: Relevance
“…Even protective stages (e.g., pellicle cysts, resting stages) that normally promote microalgal survival under adverse conditions ( Anderson and Wall, 1978 ) were negatively affected by desiccation (Table 2 ). This is in contrast with the observation of the wide geographical distribution of some of the investigated microalgal taxa, e.g., G. semen that recently expanded across lakes in Northern Europe with no water connectivity ( Lebret et al, 2015 ; Sassenhagen et al, 2015 ). Variable modes of aerosolization and different drying rates may affect microbial cells differently, as desiccation of bacterial cells aerosolized through bubble bursting was found to promote the survival in comparison to surface drying (Alsved et al, in review).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Even protective stages (e.g., pellicle cysts, resting stages) that normally promote microalgal survival under adverse conditions ( Anderson and Wall, 1978 ) were negatively affected by desiccation (Table 2 ). This is in contrast with the observation of the wide geographical distribution of some of the investigated microalgal taxa, e.g., G. semen that recently expanded across lakes in Northern Europe with no water connectivity ( Lebret et al, 2015 ; Sassenhagen et al, 2015 ). Variable modes of aerosolization and different drying rates may affect microbial cells differently, as desiccation of bacterial cells aerosolized through bubble bursting was found to promote the survival in comparison to surface drying (Alsved et al, in review).…”
Section: Discussioncontrasting
confidence: 99%
“…Taxonomy of aquatic strains was previously reported ( Logares et al, 2009 ; Rengefors et al, 2012 ; Pȩczuła et al, 2013 ; Lebret et al, 2015 ; Johansson et al, 2016 ; Karosienë et al, 2016 ) or obtained through personal communication. We identified the 81 isolated strains of airborne microalgae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the extent of population structure and its causes can be used to test between the ubiquity and moderate endemicity models, as the former predicts a lack of divergence in allopatry or isolation by distance, and little evidence for recent speciation events, in contrast to what is observed in many plants and animals. Evidence for genetically structured populations has recently been reported across a variety of taxa and habitats, including examples from ciliates (Zufall, Dimond, & Doerder, 2013), amoebae (Douglas, Kronforst, Queller, & Strassmann, 2011;Heger, Mitchell, & Leander, 2013), diatoms (Casteleyn et al, 2010;Sjöqvist, Godhe, Jonsson, Sundqvist, & Kremp, 2015;Vanormelingen et al, 2015;Whittaker & Rynearson, 2017), dinoflagellates (Lowe, Martin, Montagnes, & Watts, 2012;Rengefors, Logares, & Laybourn-Parry, 2012), raphidophytes (Lebret, Tesson, Kritzberg, Tomas, & Rengefors, 2015) and fungi (Carriconde et al, 2008;Ellison et al, 2011). While many of these studies showed clear evidence for geographic structure (supporting the moderate endemicity model), the majority were limited in resolution due to the small number of marker loci used.…”
Section: Introductionmentioning
confidence: 99%
“…Gonyostomum semen in European lakes was sometimes described as an invasive species (Hongve et al, 1988;Lepistö et al, 1994;Lebret et al, 2015), however, lack of historical records make the determination of its status very difficult. Recent studies aiming to detect resting cysts of the algae in Swedish lakes sediments with the use of PCR method, revealed that the species DNA was found in sediment depths corresponding to an age of 50 years, which suggest that the algae might be present in Swedish lakes many years before lake monitoring was started in this country (Johansson et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%